If the State provided free computer literacy, would it find takers? Evidence and propositions from the Akshaya project in India - Joyojeet Pal (Inf Syst Front (2009) 11:105-116, 2009)
The Akshaya project from Kerala has been a much discussed case for the community of practitioners and scholars working on technology and development. A unique feature of the project is its state-wide e-literacy goal in which one member of every household was trained in the telecenters set up under Akshaya at public expense. Using a survey of 1,750 households in the experimental area of Malappuram and a comparison group of neighbouring Kozhikode, this work investigates the extent of e-literacy and discusses the performance of service delivery using telecenters. While the question of whether public funds should be spent on projects such as telecenters or e-literacy continues to be an ongoing debate, the evidence here is that even though structural factors such as service delivery mechanisms and publicity make an impact on technology adoption, the overall participation in free e-literacy services among poor households remains low.